Melatonin improves the vitrification of sheep morulae by modulating transcriptome - Ji, Pengyun; Liu, Yunjie; Yan, Laiqing; Jia, Yanquan; Zhao, Mengmeng; Lv, Dongying; Yao, Yujun; Ma, Wenkui; Yin, Depeng; Liu, Fenze; Gao, Shuai; Wusiman, Abulizi; et al. (Frontiers in Veterinary Science, 2023)
In the study, for the first time, the transcriptome profiles caused by vitrification and melatonin in sheep morulae were analyzed in single embryo level. Morulae were collected from Hu sheep uterine horns after superovulation and sperm transfusion. Morulae were Cryotop vitrified and warmed. Nine morulae were in the vitrified control group (frozen), and seven morulae were vitrified and warmed with 10 -5 M melatonin (melatonin). Eleven non-frozen morulae were used as controls (fresh). After warming, each embryo was sequenced separately for library construction and gene expression analysis. p < 0.05 was used to differentiate differentially expressed genes (DEG). The results showed that differentiated differentially expressed genes (DEG) in vitrified morulae were mainly enriched in protein kinase activity, adhesion processes, calcium signaling pathways and Wnt, PI3K/AKT, Ras, ErbB and MAPK signaling pathways compared to controls. Importantly, melatonin treatment upregulated the expression of key pathways that increase the resistance of morulae against This is a provisional file, not the final typeset article vitrification induced damage. These pathways include kinase activity pathway, ErbB, and PI3K/Akt signaling pathway. It is worth mentioning that melatonin upregulates the expression of XPA, which is a key transcription factor for DNA repair. In conclusion, vitrification affected the transcriptome of in vivo-derived Hu sheep morulae, and melatonin had a protective effect on the vitrification process. These data obtained from the single embryo level provide an important molecular mechanism for further optimizing the cryopreservation of embryos or other cells.